Perspectives of Induction With Chemo and/or Immune Check Point Inhibition in Head and Neck Organ Preservation Treatment - Wiegand, Susanne; Wichmann, Gunnar; Dietz, Andreas (Frontiers in Oncology, 2019)
Induction chemotherapy (ICT) is an attractive option for advanced head and neck squamous cell carcinoma (HNSCC) patients which has been prospectively evaluated in the context of a multimodality treatment approach. The theoretical benefit is the ability to suppress distant metastases and shrink the tumor while chemotherapy is better tolerated when given sequentially than concurrently. However, clinical trials have failed to show consistent benefit of ICT over concurrent radio-chemotherapy and due to so far lacking level 1 evidence ICT outside larynx organ preservation remains rather investigational. Immune modulation by inhibition of immune checkpoints is an exciting recent development in HNSCC which has mainly been investigated as second line treatment after progression on platinum-based chemotherapy in patients with recurrent/metastatic HNSCC. Due to the promising results in these trials and even more in the first-line trial KEYNOTE-048 and encouraging first preliminary results of preoperative Anti-PD1-application, the role of neoadjuvant immunotherapy is currently under investigation in HNSCC.